An international study on the use of peroral endoscopic myotomy (POEM) in the management of esophageal diverticula: the first multicenter D-POEM experience - Yang, Juliana; Zeng, Xianhui; Yuan, Xianglei; Chang, Kenneth; Sanaei, Omid; Fayad, Lea; Kumbhari, Vivek; Singh, Vikesh; Kalloo, Anthony N.; Hu, Bing; Khashab, Mouen A. (Endoscopy, 2019)
Background The aim of this study is to report a novel, multicenter experience with the diverticular peroral endoscopic myotomy (D-POEM) technique in the management of esophageal diverticula. Methods This is a multicenter, international, retrospective study involving three centers. D-POEM was performed using the principles of submucosal endoscopy. Results A total of 11 patients with an esophageal diverticulum (Zenker’s 7, mid-esophagus 1, epiphrenic 3) were included. The mean size of the esophageal diverticula was 34.5 mm. The overall technical success rate of D-POEM was 90.9 %, with a mean procedure time of 63.2 minutes. There were no adverse events. Clinical success was achieved in 100 % (10 /10), with a decrease in mean dysphagia score from 2.7 to 0.1 (P < 0.001) during a median follow-up of 145 days (interquartile range 126 – 273). Conclusion Endoscopic management of esophageal diverticula using the novel technique of D-POEM appears promising. This first case series on D-POEM suggests that the procedure is feasible, safe, and effective in the management of esophageal diverticula. D-POEM offers the distinct advantage of ensuring a complete septotomy. Larger studies are needed to confirm these intriguing results.